INFLUENCIA DE LA TEMPERATURA DE FUSIÓN SOBRE LA DISMINUCIÓN DEL CONTENIDO DE COBRE EN LAS BARRAS DORÉ EN LA FUNDICIÓN DE PRECIPITADO ELECTROLÍTICO EN CÍA. MINERA AURÍFERA SANTA ROSA - Hilario Vergara, Kevin Iván (2018)
The copper present in ADR processes is an interfering etching as in the fusion of the electrolytic precipitate; that is why the companies that market this product (doré bars), try to reduce the presence of copper to avoid affecting their profits. The study of this project was carried out in the facilities of Compañía Minera Aurífera Santa Rosa - COMARSA with the purpose of determining the ideal temperature for an adequate melting process of the electrolytic precipitates, and thus decrease the copper content present in the doré bars , avoiding the losses of said elements in the slag produced from the melting of the electrolytic precipitates. The unifactorial model was used having as an independent variable the melting temperature of the electrolytic cement in three levels; 950º, 1050º and 1200º and as a dependent variable the percentage of copper present in doré. The results showed that as the melting temperature increases from 950ºC to 1200ºC, the presence of copper is greater in the final product; so much that at 1200ºC the presence of copper is greater than 15%, even reaching 30.54%; which will cause a serious problem at the time of commercialization of doré bars. The appropriate temperature would be 1050ºC to obtain percentages lower than 15% in copper and maximize the recovery of gold and silver, reaching an average of 99.73% of gold in the doré, and also it is possible to reduce the losses of gold and silver in the slag . It is concluded that it has been possible to improve the melting process of Gold and Silver precipitates and efficiently control the process..